2022
DOI: 10.3390/cryst12121838
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculations of the Phonon, Mechanical and Thermoelectric Properties of Half-Heusler Alloy VIrSi Alloys

Abstract: The density functional theory was used to explore the structural, electronic, dynamical, and thermoelectric properties of a VIrSi half-Heulser (HH) alloy. The minimum lattice constant of 5.69 (Å) was obtained for VIrSi alloy. The band structure and the projected density of states for this HH alloy were calculated, and the gap between the valence and conduction bands was noted to be 0.2 eV. In addition, the quasi-harmonic approximation was used to predict the dynamical stability of the VIrSi HH alloy. At 300 K,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Full-potential linearized augmented planewave method (FLAPW) was employed in Ref [32] for band structure that utilizes LAPW basis functions and the full Coulomb potential to account for all electrons (both core and valence) thereby accurately describing the electronic states near to the atomic cores and the interstitial regions between atomic sites [57]. Upon analyzing the band structure, it was observed that the conduction band minimum (CBM) of NbIrSn is situated at the X point of the Brillouin zone (BZ), while the valence band maximum (VBM) is located at the W point of the Brillouin zone (BZ) similar to that reported in VIrSi [31].…”
Section: Electronic and Magnetic Propertiesmentioning
confidence: 76%
“…Full-potential linearized augmented planewave method (FLAPW) was employed in Ref [32] for band structure that utilizes LAPW basis functions and the full Coulomb potential to account for all electrons (both core and valence) thereby accurately describing the electronic states near to the atomic cores and the interstitial regions between atomic sites [57]. Upon analyzing the band structure, it was observed that the conduction band minimum (CBM) of NbIrSn is situated at the X point of the Brillouin zone (BZ), while the valence band maximum (VBM) is located at the W point of the Brillouin zone (BZ) similar to that reported in VIrSi [31].…”
Section: Electronic and Magnetic Propertiesmentioning
confidence: 76%
“…In the present work, our primary focus is on calculating κ l of hH XNiSn (X=Ti, Zr, Hf) using Slack's equation. We obtained the required parameters for the equation from two different approaches: from elastic constants by QHA in thermo_pw code [29] implemented in Quantum ESPRESSO and the slopes of acoustical branches of phonon bands using DFPT [30].…”
Section: Introductionmentioning
confidence: 99%